NYAMUK SEBAGAI VACCINE: SEBUAH PEMIKIRAN FUTURISTIK - Kurniawati, Milla Fajar; Agustia, Fernando Dwi; Khairiskam, Muhammad; Poerwanto, Soenarwan Hery (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
The development of recombinant DNA biotechnology especially lately has opened new expectations. This technology allows to produce a vaccine that has yet to be made. In addition, this technology can also be used to improve existing vaccines, so we get more vaccine is safe and effective. This technological innovation allows the manufacture of vaccines and subunit vaccines idiotipe (therapeutic vaccines). Therefore, we initiated the concept of mosquitoes as Vaccine Delivery Host: A Futuristic Thought as the protection of effective prevention and control as a solution to the crisis facing outbreaks of infectious and parasitic diseases that occur in Indonesia. This concept utilizes a mosquito vector for the production of antigens by recombinant DNA techniques. Where specific antigens of microbial parasites were cloned in bacterial plasmids engineered to increase expression of the inserted gene in the cells of the mosquito vector, so that when the mosquito bites do not transmit disease, but actually increase the immune response to a disease. The aim of this concept is in addition to the protection and control of outbreaks of infectious diseases and parasitic diseases in endemic areas, it is also said in response to the health crisis in contemporary conditions.Keywords: mosquito vector, recombinant DNA, vaccine